2015
DOI: 10.18510/gctl.2015.114
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Some Mineral Profile of Honey Marketed and Consumed in Some of the States in Northern Part of Country (Nigeria)

Abstract: Honey and honey trade is an important economic activity for many tropical rural and urban areas worldwide. In West Africa and other part of the world, honey and honey products holds high socio–cultural, religious, medicinal and traditional values. Therefore, to maximize benefits or to enhance profit, a variety of components are added to the raw, fresh and unprocessed honey, introducing the possibility of heavy metals contaminants. Therefore the honey sold in various places, markets and shops  in some states in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Despite having essential minerals, the honeys had heavy metals with concentrations above maximum permissible limits. Ba, Fe, Pb, Cr, Ni, Ag, Mn, Cd and As were above recommended limits similar to the reports of Obasi et al (2020) in the South east, and Odoh et al (2015) in the middle belt. This calls for further public health concern and detailed investigation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Despite having essential minerals, the honeys had heavy metals with concentrations above maximum permissible limits. Ba, Fe, Pb, Cr, Ni, Ag, Mn, Cd and As were above recommended limits similar to the reports of Obasi et al (2020) in the South east, and Odoh et al (2015) in the middle belt. This calls for further public health concern and detailed investigation.…”
Section: Discussionsupporting
confidence: 88%
“…To our knowledge, very little or no empirical research on the elemental composition of honey has been carried out in Nigeria, and only recently, Obasi et al (2020) reported the presence of heavy metals in apiary honeys from south-eastern Nigeria with Arsenic and Lead levels above recommended range in some of the samples posing potential health risk for children. Odoh et al (2015) report also covered the middle belt region of Nigeria (Taraba, Nassarawa, FCT and Abuja) con rming the presence of honeys from that region.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation